METHODS OF TEACHING MATHEMATICS IN PRIMARY EDUCATION - Qurbonov Fazliddin Botirovich (Web of Journals Publishing, 2023)
The article discusses ways to improve the effectiveness of mathematics teaching in elementary grades based on the resources that students can learn from. At the same time, the effective use of several methods is shown as an example.
Keywords: method, discussion, explanation, induction, deduction, analogy, analysis, synthesis, comparison, problematic, explanatory, illustrative, reproductive.